Covid-19 and its impacts on consumer decision-making process - Hashim, Norashuha; Hasim, Muhammad Asyraf; Harun, Amran (Penerbit UTHM, 2022)
The term "virus" derives from the Latin word for "venom" and refers to a microscopic infectious agent. On the other hand, "corona" is named by its shape to look like a crown ring – the scientists who coined the word coronavirus in 1968 reasoned that the virus they were studying under a microscope resembled a solar corona (Steinmetz, 2020). COVID-19 was introduced when it was first detected in late 2019 and used letters from CO-Rona-VI-rus D-isease (Bhargava, 2020). Corona infections were initially seen as cold in 1965 (Kahn & McIntosh, 2005), which is almost six decades ago. Corona was formerly thought to be a basic, non-fatal virus to human beings until 2002. Before the world witnessed a Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) outbreak in November 2002, it was assumed that this virus mainly infected animals. However, this was proven incorrect. Ten years after that, a new pathogenic coronavirus known as the Middle East Respiratory Syndrome Coronavirus (MERS-CoV) spread throughout the Middle East and caused a pandemic in several countries (Shereen et a., 2020).